Significance of Granting Legal Personality to Waqf Establishments in The Republic of Guinea - Mohamed Sano (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. It is seen that while some countries have figured out the elements necessary to ensure the effective operation of waqf entities, most have yet to do so. The situation in the Republic of Guinea is that all waqf facilities in the country, with the exception of Waqf IDB Guinea, have been deprived of a ‘legal personality’ status, putting a cap on the great potential that could be realized. To address this issue, the study has looked into and cross-examined the status of waqf in different countries and has, accordingly, proposed that the ‘legal personality’ status be awarded to waqf facilities in Guinea so as to attract the relevant stakeholders, render legal recourse available to aggrieved parties, register the beneficial interest of relevant participants, and lastly create job, investment and other opportunities for interested parties. Such measure, as has been proven, would greatly benefit the Guinean society and other communities.Keyword: Waqf, legal personality, Republic of Guinea, Islamic finance. Abstrak. Terlihat bahwa sementara beberapa negara telah menemukan elemen-elemen yang diperlukan dalam kerangka tata kelola wakaf mereka, yang lain belum melakukannya. Di Republik Guinea, entitas wakaf tertentu yang diakui secara hukum yang dikenal sebagai Wakaf IDB Guinea telah memprakarsai banyak proyek. Namun, terlepas dari entitas tersebut, fasilitas wakaf di negara ini telah dicabut status 'subyek hukum'-nya, yang telah membatasi potensi besar yang dapat direalisasikan. Untuk mengatasi masalah ini, penelitian mengusulkan agar status 'subyek hukum' diberikan kepada fasilitas wakaf di Guinea untuk menarik minat para pemangku kepentingan, memberikan jalan hukum yang tersedia bagi pihak yang dirugikan, mendaftarkan manfaat waqaf bagi para pihak yang berkepentingan, dan terakhir menciptakan lapangan kerja, investasi dan peluang lain untuk para pihak yang berkepentingan. Pemberian status badan hukum kepada lembaga-lembaga wakaf, sebagaimana telah dibuktikan, akan sangat bermanfaat bagi masyarakat Guinea dan masyarakat lainnya.Kata Kunci: Waqf, Subyek Hukum, Republik Guinea, Keuangan Syariah.